24. RESULTS OF TREATMENT OF BLEEDING IN CESAREAN SECTION BY UTERINE ARTERY LIGATION AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the results of treatment of bleeding during cesarean section by uterine artery ligation at the National Hospital of Obstetrics and Gynecology from June 2021 to May 2023.Research subjects and methods: Retrospective study of data based on medical records of 250 pregnant women who underwent uterine artery ligation to treat bleeding during cesarean section at the National Hospital of Obstetrics and Gynecology from June 2021 to May 2023.Results: Uterine artery ligation was highly successful in cases of postpartum bleeding during cesarean section at National Hospital of Obstetrics and Gynecology (87.6%). The age of the pregnant woman, the need for blood transfusion and polymer solution infusion are related to the success rate of the procedure.Conclusion: Uterine artery ligation can be widely applied to stop bleeding during cesarean section. Attention should be paid to assessing the characteristics of pregnant women as well as disseminating and improving techniques among surgeons to ensure optimal treatment results.
Keywords: Postpartum bleeding; hemostasis; uterine artery ligation; cesarean section